حساب وتحليل كمية الاشعاع الساقط على السطح الافقي لمدينة الناصرية - رمضان رسول (University of Thi-Qar Journal of Science, 2010)
This research involves an applied study to be executed on the lands using complex of Solar Cells to get the needed energy from the total solar irradiance quantities that reach the horizontal surface of al- Nasiriyah city for the unit area taking into account the metrological data as temperature , humidity , dust. and for the interval 1/1/2007 – 1/1/2008 taken from al- Nasiriyah metrological data station with the geographical data as longitude & latitude (46.14,31.15) respectively ,which have a direct effect for the sun slop light. The results show that the solar irradiance was about 0-543 watt/m 2 as a minimum and maximum measured values, the process of absorption, scattering, and water vapor take effect on it directly.